1972
DOI: 10.1007/bf00040553
|View full text |Cite
|
Sign up to set email alerts
|

The inheritance of resistance to blue mold (Peronospora tabacina Adam) in two cultivars of tobacco (Nicotiana tabacum L.)

Abstract: Two blue-mold resistant cultivars of Nicotiuna tabacum L. were crossed with each other and with the susceptible Israeli local cultivar Mikhal. F1, F, and F3 progenies of these crosses, F1 and Fz of backcrosses and the parental varieties were grown in a series of experiments, in which the seedlings were exposed to heavy natural infection with Peronospora tabacina ADAM. The genetic basis of resistance was found to be identical in the two resistant strains Bel-61-10 and Chemical mutant. A single dominant major ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…These data suggest that resistance in Chemical Mutant may be due to alien gene introgression rather than induced mutation. Indeed, Marani et al (1972) found no segregation for blue mold resistance in progeny derived from the cross Bel 61‐10/Chemical Mutant, a result suggesting that genetic factors conditioning resistance in these two lines were identical. As noted by Rufty (1989), it is unlikely that a resistance allele derived via mutation breeding would occur at the same genome position as that which possesses a gene introgressed from a wild Nicotiana relative.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…These data suggest that resistance in Chemical Mutant may be due to alien gene introgression rather than induced mutation. Indeed, Marani et al (1972) found no segregation for blue mold resistance in progeny derived from the cross Bel 61‐10/Chemical Mutant, a result suggesting that genetic factors conditioning resistance in these two lines were identical. As noted by Rufty (1989), it is unlikely that a resistance allele derived via mutation breeding would occur at the same genome position as that which possesses a gene introgressed from a wild Nicotiana relative.…”
Section: Discussionmentioning
confidence: 96%
“…Our marker data suggest that N. debneyi may be the true donor of resistance in Ovens 62 as well as in Sirone, Sirogo, ZA 684, ZA 692, Sota 6505, and Bel 6‐10. It was interesting that all 12 coupling phase RAPD markers linked to a factor controlling blue mold resistance in Ovens 62 were also present in lines with resistance supposedly achieved via induced mutation (Marani et al, 1972). These data suggest that resistance in Chemical Mutant may be due to alien gene introgression rather than induced mutation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations